Plan estratégico de comunicación interna para Ilven Internacional - Moreno Gutiérrez, Angélica Alexandra (2014)
The present project was done to ILVEM International, the proposal was internally consider by the company. Among the activities undertaken the development of a full research staff currently providing services was proposed. As results of the research on which important results were plotted by statistical tables and charts were obtained. The research results allowed to propose measurable objectives, which were raised based on the knowledge acquired during the development of expertise. The general and specific objectives, are part of a comprehensive internal communications plan, it responds to the hypothesis proposed. As part of this study, the literature review was used by different authors , they were cited to support the development of the thesis project. The feasibility of this work is measured in terms of the same indicators proposed are measurable and achievable within the time limits.